1,1'-Butane-1,4-Diylbis(1H-Benzimidazole) - Akkurt, M.; Karaca, S.; Küçükbay, H.; Büyuk̈güngör, O. (Blackwell Publishing, 2007)
The molecule of the title compound, C18H18N 4, is disposed about a center of inversion. The dihedral angle between the five- and six-membered rings is 1.23 (6)°, showing almost exact coplanarity. © 2007 International Union of Crystallography All rights reserved.